2020
DOI: 10.5603/fm.a2019.0088
|View full text |Cite
|
Sign up to set email alerts
|

Splenic artery angiography: clinical classification of origin and branching variations of splenic artery by multi-detector computed tomography angiography method

Abstract: Background: The splenic artery (SA) variations are rarely reported in the literature. Knowledge of the range of the SA and other arterial anomalies and their specific frequencies is very important ever for every visceral surgeon as well as for treatment of gastrointestinal bleeding, organ transplantation, transarterial chemoembolisation of neoplasm, infusion therapy, therapeutic arterial ligation, iatrogenic injuries. At the literature, there are more studies on the coeliac trunk, superior mesenteric artery an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…All of these procedures are based on a deep understanding of both the anatomy of the organ and the region as a whole. Knowing the variants of the splenic artery is particularly important for visceral surgeons, due to its frequent involvement in gastrointestinal bleeding, organ transplantation, trans-arterial chemoembolization of neoplasms, infusion therapy and iatrogenic injuries [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All of these procedures are based on a deep understanding of both the anatomy of the organ and the region as a whole. Knowing the variants of the splenic artery is particularly important for visceral surgeons, due to its frequent involvement in gastrointestinal bleeding, organ transplantation, trans-arterial chemoembolization of neoplasms, infusion therapy and iatrogenic injuries [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The trajectory of the splenic artery is variable. There are three main types of trajectories: straight, sinuous and spiral [ 10 ]. One or more loops are observed in up to 83–86% of spleens [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…3,4 The risk factors for SAA include portal hypertension, female hormones such as estrogen, and severe flexion. 5 It was observed that SAAs are four times more frequent in women. Although an indication for treatment of SAA has not been generally established, surgery is usually adopted for ruptured or symptomatic aneurysms, pseudoaneurysms, rapid enlargement, and aneurysms with a diameter over 2 cm as well as for women with childbearing potential.…”
Section: Discussionmentioning
confidence: 99%
“…Ekingen et al 1 published a new classification system documenting 22 different splenic artery types by computed tomography angiography. The splenic artery arising from the superior mesenteric artery (SMA), known as the splenomesenteric trunk, occurred in 0.13% of 750 patients (type 8).…”
mentioning
confidence: 99%
“…The splenic artery arising from the superior mesenteric artery (SMA), known as the splenomesenteric trunk, occurred in 0.13% of 750 patients (type 8). 1 Few case reports have described treatment of these aberrant SAA with coil embolization, 2 endovascular exclusion with a covered stent, 3 or a combination of the 2, depending on aneurysm morphology and origin.…”
mentioning
confidence: 99%